Global and Regional Spillovers to GCC Equity Markets - Saadi Sedik, Tahsin (IMF Working Papers; Working Paper, 2011)
This paper analyzes the impact of global and regional spillovers to GCC equity markets. GCC equity markets were impacted by spillovers from U.S. equity markets despite varying degrees of foreign participation. Spillovers from regional equity markets were also important but the magnitude of the effects were on average smaller than that from mature markets. The results also illustrated episodes of contagion in particular during the recent global financial crisis. The findings suggest that given the degree of openness, and open capital accounts the financial channel is an important source through which volatility is transmitted. In this regard, GCC equity markets are not immune from global and regional financial shocks. These findings refute the notion of decoupling between the GCC equity and global equity markets.